Wpływ techniki sadzenia na efekty rekultywacji składowiska popiołów elektrownianych = Impact of planting technique on reclamation of disposal site of power station incineration ash - Gilewska, Mirosława; Otremba, Krzysztof (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper considers the researches of biological reclamation of incineration ash disposal site of Adamów power station. The results indicates that application of gray boulder clay of Middle Poland glaciation and sewage sludge to dressing of holes dug in ash rock is an effective method. The more so this method is much cheaper than covering all of the area by these materials.
Keywords: składowisko popiołów elektrownianych; skała popiołowa; glina zwałowa; osady ściekowe; rekultywacja; disposal site of power station incineration ash; ash rock; boulder clay; sewage sludge; reclamation